Comparison of two microscopic interpretations of vaginal microbiota with molecular profiling - Durski, Mariana; Ravel, Jacques; Spautz, Ana C.P.G.; Carvalho, Newton S.; Silva, Márcia G. [UNESP]; Marconi, Camila [UNESP] (Elsevier, 2022)
Objective: To compare the diagnosis of bacterial vaginosis (BV) by Nugent scoring criteria (Nugent-BV) and the diagnosis of BV and/or aerobic vaginitis (AV) using Donders criteria (Donders-BV/AV) for identifying Molecular-BV detected by bacterial 16s rRNA profiling. Methods: We enrolled 512 women of reproductive age in Brazil with data available on Nugent and Donders microscopic analysis and 16S rRNA sequencing. We constructed receiver operating characteristic (ROC) curves of Nugent-BV and Donders-BV/AV and calculated their area under the curves (AUCs) and 95% confidence interval (CI) for matching Molecular-BV. Results: A total of 155 (28.7%) participants were positive for Nugent-BV. Donders-BV and -AV were detected in 90 (17.6%) and 75 (14.6%) participants, respectively, while 28 (5.5%) had concurrent Donders-BV and -AV. Molecular-BV was identified in 139 (27.1%) participants. Analysis of ROC curves showed that diagnosis of Nugent-BV more accurately aligned with presence of Molecular-BV (AUC: 0.88, 95% CI: 0.84–0.91) when compared to Donders-AV/BV (AUC: 0.84; CI: 0.80–0.87) (P = 0.005). Conclusion: The use of Nugent-BV is more representative of Molecular-BV than Donders-AV/BV.
Keywords: 16S rRNA gene; aerobic vaginitis; bacterial vaginosis; microscopy; molecular diagnostics; vaginal microbiota